ANALISIS RATA GRADE POINT BERBASIS PEMILIHAN PENDAFTARAN MAHASISWA BARU FAKULTAS EKONOMI UNJ (2017) - Tuty Sariwulan (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The objective of this study is to analyze the students which taking classes on time four years and analyze the Grade Point Average based on new students registration selection into four ways, namely: SNMPTN, SBMPTN, PENMABA and Exchange Program Faculty of Economics UNJ. This study uses a quantitative approach with descriptive method of presentation that uses a form of tables and graphs histogram to make it easier to analyze the data. From the results of calculations using the comparison in terms of percentage, the results are: students with SNMPTN have a larger percentage amount for studying on time compared with SBMPTN. Similarly, SBMPTN students have a number greater than the percentage of PENMABA or Exchange Program. For the Grade Point Average above 3.5, SBMPTN has a greater percentage when compared with SNMPTN. Conversely, the Exchange Program has the lowest percentage of on time study completion compared with the other pathways. While the Grade Point Average is the has the highest second position after SBMPTN. Overall with a total of 708 students, 403 students or 56.9% on time in completing the study.